PENGARUH KEGIATAN BELAJAR MEMBACA TERARAHTHERHADAP KEMAMPUAN MURID KELAS DUA SMP BABUSSALAM DALAM MEMAHAMI RECOUNT TEKS - Rahmad Hanif; Fakhri Ras; Erni Erni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This pre experimental research is aimed at finding out the effects of Directed Reading Thinking Activity (DRTA) on the reading comprehension ability of the second year students of SMP Babussalam Pekanbaru. The participants were 20 students of the second year students of SMP Babussalam Pekanbaru who have similar characteristic in term of academic achievement and age factors. This research was conducted from 16 January to 31 January 2018. It took place in SMP Babussalam Pekanbaru which is located at Jl. H.R Soebrantas , Pekanbaru. The data were collected by using pre-test and post-test. The data were analyzed by using SPSS(Statistical Product and Service Solutions ). The research finding of this research showed that there is significant effect of Directed Reading Thinking Activity on the reading comprehension ability of the second year students of SMP Babussalam Pekanbaru. The Post-Test result (77.25) was higher than Pre-Test result(58.37). The differences between the mean scores of pre-test and post-test is as big as 18.88.The result also showed that the value of t-test (9.68) was higher than t-table (2.086) at the significance level 5 %. Therefore ,the hypothesis was accepted . Hence, there is an effect of Directed Reading Thinking Activity on the reading comprehension ability of the second year students of SMP Babussalam Pekanbaru.Keywords: Directed Reading Thinking Activity(DRTA), Reading comprehension, Recount text